LEGAL PROTECTION FOR CONSUMERS IN E-COMMERCE TRANSACTIONS - Riza Firdaus; Dahlan (Universitas Efarina, 2024)
The development of business law is currently growing very rapidly. In addition, the development of advanced technology and law must follow the times. In Indonesia, online transactions (e-commerce) have begun to develop. Legal protection for consumers has been regulated in Law Number 8 of 1999 and electronic information and transactions are regulated in Law Number 1 of 2024. In relation to this, there are two problems, the first is whether Law Number 8 of 1999 concerning Consumer Protection and Law Number 1 of 2024 concerning ITE have provided protection for consumers in conducting online transactions (e-commerce). Second, How is the legal protection for consumers in online transactions (e-commerce). The methodology used in this study uses a normative approach which is used as material in written regulations so that this study is very closely related to literature studies that require secondary data. The conclusion of the research conducted is that Law No. 8 of 1999 and Law No. 1 of 2024 can protect consumers because the provisions contained in this law have accommodated consumer rights in this transaction. The government should revise Law No. 8 of 1999 so that it can protect not only conventional transactions but also e-commerce transactions and not only cover the territory of Indonesia but also include international transactions regarding the path that consumers can take if a dispute occurs to obtain legal remedies non-litigation through YLKI and BPSK.